The Optimum Powder Loading of Different Binder Ratio Between LDPE and RWL as Binder in Metal Injection Molding - Badrul Hisham, Muhammad Aminin Umair; Azriszul Mohd Amin, (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Metal Injection Molding (MIM) is a manufacturing technique that utilizes powdered metal and polymer as a feedstock to create intricate shapes for a single component. The selection of the appropriate binder in Metal Injection Molding (MIM) formulation holds utmost importance in ensuring the production of top-notch and durable components. This study is focused on evaluation homogeneity variation of feedstock for different binder ratio and determination optimal powder loading for different binder ratio. The binder formulation of LDPE and RWL being selected here are 60/40, 50/50 and 40/60 accordingly with the powder loading 80 percent to 90 percent for each binder formulation. The analysis will be based on density measurement and Scanning Electron Microscopy (SEM). Furthermore, different binder ratio depicts on different optimal powder on volumetric powder loading. The best powder loading for the 60/40 binder formulation of LDPE and RWL is achieved at 84 percent, corresponding to a density of 1.808 (g/cm3) at a specific point. Similarly, for the 50/50 binder formulation, the optimum powder loading is 86 percent at a density of 1.741 (g/cm3) at a different point. Lastly, the 40/60 binder formulation attains the best uniformity graph of homogeneity feedstock with an optimal powder loading of 86 percent at a density of 1.945 (g/cm3) at yet another point. The range of density presented smaller compared to the other. The integrity, reliability, and performance of the final components are directly affected by homogeneity.